PENGARUH PEMBERIAN REWARD TERHADAP KEDISIPLINAN GURU DI SDN 34 MANDAU KABUPATEN BENGKALIS - Leniwati (Jurnal PAJAR (Pendidikan dan Pengajaran), 2021)
The purpose of this study was to improve teachers’ discipline in the learning process through the provision of rewards. This research was a school action research conducted by the principal and carried out in two research cycles. The subjects of this study consisted of 14 teachers at SDN 34 X. The results showed that giving rewards to teachers improved teachers’ discipline in teaching, especially in terms of punctuality in coming to school. This was proven by the analysis of teachers’ discipline, which showed a percentage of 56% in the aspect of learning implementation, 92.3% in the aspect of controlling behavior, and 84.6% in the aspect of punctuality. Overall, the percentage of teachers’ discipline in learning reached 83% and was categorized as “Good.” These results were also supported by observations of teachers’ activities conducted over two learning cycles. The findings revealed that in the first cycle, the percentage of teachers’ activity in the first meeting was 52% with an “unfavorable” category, increasing to 62% with a “fairly good” category in the second meeting. Furthermore, the percentage continued to increase in the second cycle, reaching 83% with a “good” category in the third meeting and significantly increasing to 92% with a “very good” category in the fourth meeting. Thus, it was proven that the provision of rewards effectively improved teachers’ discipline in teaching activities at SDN 34 X.